Pengaruh Brand Ambassador Dan Strategi Marketing Terhadap Loyalitas Pelanggan (Studi Pada Boyband Neo Culture Technology Dream Produk Tostos Di Jakarta) - Sukarni Novita Sari; Meishela Husna Dewi; Juardi Juardi (Jaanur Elbarik Indonesia, 2026)
This study aims to find out and analyze how much influence Brand Ambassador and Marketing Strategy on Customer Loyalty in Tostos products by studying the NeoCulture Technology Dream (NCT Dream) band, especially in the Lotte Mall Avenue Jakarta area. This research method uses a quantitative approach with survey techniques through the distribution of questionnaires to 180 respondents. In this study, the data test uses a validity test, a reliability test, a classical assumption test in which there is a normality test, a multicollinearity test, and a heteroscedasticity test, then a multiple linear regression analysis test with a t test and an f test, as well as a determination coefficient test. The results of the study show that Brand Ambassadors have an effect on Customer Loyalty with a contribution of 7.8%. Marketing strategy also has a positive and significant influence with a contribution of 16.5%. Simultaneously, both variables exerted an influence of 16.6% on Customer Loyalty, where Marketing Strategy had a more dominant influence